BANKRUPTCY RISK ASSESSMENT FOR INSURANCE COMPANIES UNDER UNCERTAINTY - Zatonatska, Tetiana; Anisimova, Olga; Zatonatskiy, Dmytro; Vorontsova, Daryna (Socio-economic relations in the digital society, 2023)
The insurance market is an integral part of the country’s financial system and is therefore extremely important for economic development. Any shocks in the insurance market may cause a slowdown in economic growth and development and have a negative impact on the country’s financial system. The stability of the insurance market is ensured by the companies operating in it. That is why our analysis focuses on assessing the risk of insurance companies’ bankruptcy and analyzing the main factors that affect the situation in the insurance market. This article analyzes the main approaches to assessing the risk of insurance companies depending on the size of the risk premium. A simple dynamic risk assessment model was applied. Our analysis of the literature has shown that general approaches to assessing the risk of insurance company failure depend on the overall situation in the country and the market itself. In countries with more frequent force majeure events, more complex and sophisticated models have been introduced to assess the required amount of risk premium to avoid bankruptcy. The market situation in Ukraine had been stable for a long time, but with the onset of the pandemic, certain problems began to arise. An analysis of one of the leading insurance companies in the market showed that before the war started, it had a bankruptcy risk close to zero. Unfortunately, it should be noted that military actions, which are force majeure circumstances, complicate the quantitative analysis, as Ukrainian companies do not have effective mechanisms to cover this type of risk. It is established that a company cannot arbitrarily determine the amount of risk premium based on its own needs. This value will also be influenced by external macroeconomic factors that will affect not only the overall economic situation but also all participants in the insurance market, including consumers of insurance services.